1997
DOI: 10.1590/s0100-879x1997001100017
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying of liquids in rats dehydrated by water deprivation

Abstract: The gastric emptying of liquids was investigated in male Wistar rats (8 to 10 weeks old, 210-300 g) dehydrated by water deprivation. In this model of dehydration, weight loss, hematocrit and plasma density were significantly higher in the dehydrated animals than in the control groups after 48 and 72 h of water deprivation (P<0.05). Three test meals (saline (N = 10), water (N = 10) and a WHO rehydrating solution containing in one liter 90 mEq sodium, 20 mEq potassium, 80 mEq chloride and 30 mEq citrate (N = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…The increase in GE rates was also reversed by the infusion of the shed blood, in agreement with previous experiments (22), suggesting that the effect of bleeding on GE was BV dependent. In contrast to our findings, it has been observed that GE of liquid is delayed in rats submitted to chronic (72 h) water deprivation (24). These differences may be explained by the activation of different neurohumoral pathways, since our experiments were performed under acute conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…The increase in GE rates was also reversed by the infusion of the shed blood, in agreement with previous experiments (22), suggesting that the effect of bleeding on GE was BV dependent. In contrast to our findings, it has been observed that GE of liquid is delayed in rats submitted to chronic (72 h) water deprivation (24). These differences may be explained by the activation of different neurohumoral pathways, since our experiments were performed under acute conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the difference between the fasting groups occurred probably due to simply hydration of the gastric contents 15 , giving the false impression of a larger quantity of food.…”
Section: Discussionmentioning
confidence: 99%